Phosphorylation of Human Immunodeficiency Virus Type 1 Vpr Regulates Cell Cycle Arrest - Zhou, Yi (American Society for Microbiology, 2000)
Human immunodeficiency virus type 1 (HIV-1) Vpr regulates nuclear transport of the viral preintegration complex, G(2) cell cycle arrest, and transcriptional transactivation. We asked whether phosphorylation could affect Vpr activity. Vpr was found to be phosphorylated on serine residues in transiently transfected and infected cells. Residues 79, 94, and 96 were all found to be phosphorylated, as assessed by alanine mutations. Mutation of Ser-79 to Ala abrogated effects of Vpr on cell cycle progression, whereas mutation of Ser-94 and Ser-96 had no effect. Simultaneous mutation of all three Vpr serine residues attenuated HIV-1 replication in macrophages, whereas single and double Ser mutations had no effect.